Combustion studies in a fluidised bed—The link between temperature, NOx and N2O formation,char morphology and coal type - Valentim, B. (2007)
Five commercially available high volatile bituminous coals from different origins were studied with the objective of characterizing their petrographic nature with respect to emissions of NOx and N2O. The chars produced [at temperatures ranging from 700 to 1000 °C] from these coals were also petrographically analyzed to assess the contribution of char to NOx and N2O formation during combustion. Vitrinite-rich coals produced higher porous chars (cenospheres and tenuinetworks) than those that are rich in inertinite. The former coals were, however, found to release lower concentrations of NO. Consistent with previous works, N2O emissions were observed to decrease significantly with temperature, however, on the whole, the N2O emissions from vitrinite-rich high volatile coals were less than those from inertinite-rich coals. Additionally, high porous chars were found to give rise to lower emissions of NO and N2O.